Market Strategy in Competition in Islamic Financial Institutions - Yudhi K. Noorhidayat (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Entering a new era of economic and trade relations at the national, regional, and international levels, it is necessary to understand marketing and the right strategies to achieve marketing targets. On the other hand, in the field of Islamic institutions in Indonesia, there are several obstacles or problems including human resource problems and inappropriate marketing strategies. So it is necessary to improve the quality of human resources and several efforts in carrying out appropriate marketing strategies, including marketing mix strategies, marketing segmentation, radical marketing, and the creation of spiritual advocates. This research used descriptive qualitative research which aimed to find out how to use the right marketing strategy in the international arena, and how Islamic institutions can use the right marketing to encourage increased market share in the midst of global competition. The results of the study indicated that there are several marketing strategy efforts that can be carried out and developed, including through marketing mix strategies, marketing segmentation strategies, radical marketing strategies, creating spiritual advocates, and human resource development strategies.